Unexpectedness: “What the Music Could Be”—Revisiting the Unexpectedness of Jim Pepper - Perea, John-Carlos; Perea, Jacob E. (Kalfou (Santa Barbara, Calif.), 2019)
The concepts of expectation, anomaly, and unexpectedness that Philip J. Deloria developed in Indians in Unexpected Places (2004) have shaped a wide range of interdisciplinary research projects. In the process, those terms have changed the ways it is possible to think about American Indian representation, cosmopolitanism, and agency. This article revisits my own work in this area and provides a short survey of related scholarship in order to reassess the concept of unexpectedness in the present moment and to consider the ways my deployment of it might change in order to better meet the needs of my students. To begin a process of engaging intergenerational perspectives on this subject, the article concludes with an interview with Dr. Jacob E. Perea, dean emeritus of the Graduate College of Education at San Francisco State University and a veteran of the 1969 student strikes that founded the College of Ethnic Studies at San Francisco State University.